2011
DOI: 10.1080/09084282.2011.595457
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Injury-Related Moderators of Memory and Achievement Outcome in Pediatric TBI

Abstract: Critical factors affecting traumatic brain injury (TBI) outcome in children and adolescents are explored with an emphasis on an examination of age at injury as a predictor of memory functioning. Age at injury and other injury-related and demographic predictors (i.e., severity, time postinjury, gender, and socioeconomic status [SES]) of memory and achievement outcome were examined in 65 children and adolescents post-TBI compared to 65 age-matched noninjured controls. Although robust findings have been found for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This is the first investigation into the influence of microstructural damage to white matter on the relationship between injury severity and long-term verbal memory outcome following pediatric TBI. It is well known that extensive structural damage and persistent cognitive dysfunction are more likely to result from more severe injuries (Anderson et al 2012;Faber et al 2016;Ghosh et al 2009;Lajiness-O'Neill et al 2011;Wilde et al 2012;Wilde et al 2015;Yeates et al 2017), but the knowledge of the specific contributions of these factors toward cognitive outcome is sparse. This is particularly true concerning damage to the developing brain, even though it is the most common cause of childhood disability (Cuff et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first investigation into the influence of microstructural damage to white matter on the relationship between injury severity and long-term verbal memory outcome following pediatric TBI. It is well known that extensive structural damage and persistent cognitive dysfunction are more likely to result from more severe injuries (Anderson et al 2012;Faber et al 2016;Ghosh et al 2009;Lajiness-O'Neill et al 2011;Wilde et al 2012;Wilde et al 2015;Yeates et al 2017), but the knowledge of the specific contributions of these factors toward cognitive outcome is sparse. This is particularly true concerning damage to the developing brain, even though it is the most common cause of childhood disability (Cuff et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the months following a pediatric TBI, GCS is a good predictor of cerebral atrophy, which is a sensitive measure of white matter volume loss (Ghosh et al 2009). An inverse relationship between injury severity and cognitive outcome is consistently documented in pediatric TBI, where verbal memory is shown to be a key predictor of long-term academic success (Lajiness-O'Neill et al 2011). In terms of more specific cognitive outcome, Anderson and Catroppa (2007) demonstrated a negative relationship between pediatric TBI severity and performance on measures of verbal learning and memory.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that young adults in the high-SES TBI group exhibited similar social cognition skills to noninjured high-SES participants and significantly better performance when compared to the low-SES TBI group [ 19 ]. Other studies have also indicated that SES is a significant contributor to other outcomes (i.e., memory, behavior, adaptive ability, reading, and spelling) following a severe TBI (see Anderson et al [ 44 ] and Lajiness-O'Neill et al [ 45 ]). It should be noted that some investigators have speculated that lower SES may increase the risk of TBI [ 46 ] potentially increasing the complications and economic burden of TBI for this portion of the population.…”
Section: Dynamic Protective Factorsmentioning
confidence: 99%
“… 1 , 2 The common disabilities of patients include sensory and motor deficits and cognitive problems, 3 which are commonly induced by several pathological events such as necrosis, apoptosis, and excessive autophagy. 4 , 5 Disconnection of neural circuits from axonal injury in the central nervous system (CNS) is the chief reason for neurological impairments, 6 , 7 Therefore it is necessary to search for an effective therapy to reduce TBI-related disabilities. To date, biological therapy based on stem cell transplantation has been used in experimental research of CNS disorders like TBI.…”
Section: Introductionmentioning
confidence: 99%